Augmented Reality in Primary Education: Exploring Teachers’ Readiness and Needs for Innovative Learning Media - Rizki Nurazmi Fadhilah Diyaurrahman; Alfi Laila; Bagus Amirul Mukmin (FKIP UNIVERSITAS PAKUAN, 2025)
The rapid advancement of modern technology has had a significant impact on various sectors, including education. This study aims to analyze the teacher readiness and needs to find the inovative augmented reality (AR)-based learning media in elementary schools. Using a qualitative approach, data was collected through classroom observations, In-depth interviews with 57 teachers., and needs assessment questionnaires from 684 fifth grader students who currently use conventional teaching media. The data was analysed using thematic analysis to identify patterns and themes that emerged from students and teachers’ needs and preferences regarding learning media. The findings show that there is a need for more interactive and immersive learning media, which can help students understand abstract concepts more effectively. Students' preference for dynamic learning media, such as videos, animations, and interactive simulations, was identified as a solution to improve material understanding. These results suggest that AR has the potential to be a powerful tool to improve student participation and learning outcomes, making the learning process more adaptive and responsive to individual needs.